2021
DOI: 10.1016/j.nedt.2020.104623
|View full text |Cite
|
Sign up to set email alerts
|

A review of virtual-simulation for assessing healthcare students' clinical competency

Abstract: Highlights• Simulation in medical programs was often task focused, whilst in nursing programs focus was to develop critical thinking• Online student debriefing is an important part of the learning process in virtual simulation• A virtual world enables students to learn complex clinical reasoning in a safe environment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 48 publications
4
49
0
1
Order By: Relevance
“…Further, participants reported that the detailed personalized feedback log and guided reflection questions in VS helped them to evaluate their knowledge level and to reflect on their strengths and areas in which they needed improvement. This finding supports the assertion by Coyne et al (2020) that virtual simulation should incorporate reflection, and it underscores the importance of providing opportunities for nursing students to self-evaluate. Participants preferred to receive feedback from the instructor as well as a debriefing session with the instructor and their peers, supporting the finding by Verkuyl et al (2017) that debriefing is an essential component of simulation-based learning.…”
Section: Discussionsupporting
confidence: 85%
“…Further, participants reported that the detailed personalized feedback log and guided reflection questions in VS helped them to evaluate their knowledge level and to reflect on their strengths and areas in which they needed improvement. This finding supports the assertion by Coyne et al (2020) that virtual simulation should incorporate reflection, and it underscores the importance of providing opportunities for nursing students to self-evaluate. Participants preferred to receive feedback from the instructor as well as a debriefing session with the instructor and their peers, supporting the finding by Verkuyl et al (2017) that debriefing is an essential component of simulation-based learning.…”
Section: Discussionsupporting
confidence: 85%
“…Aktuelle Übersichtsarbeiten zeigen, dass es sich bei den in der Pflegebildung verwendeten VR überwiegend um Trainingsumgebungen handelt, in denen klinische Szenarien (Arbeitsprozesse oder Handlungen) simuliert werden (Liaw et al 2018, Weiß et al 2018, Bracq et al 2018, Fealy et al 2019, Kyaw et al 2019, Zhang et al 2019, Foronda et al 2020, Rourke et al 2020, Chen et al 2020, Coyne et al 2021…”
Section: Vr-anwendungen In Der Pflegebildungunclassified
“…Simulation is also presented as an appropriate educational method for the replacement of clinical practicums, as the number of clinical sites is limited [ 2 ]. In addition, simulations can be presented as online clinical courses in situations in which it is difficult to present clinical practicums or simulation-based education in a face-to-face manner, e.g., during the coronavirus disease 2019 pandemic [ 3 , 4 ]. Systematic reviews have indicated that high-fidelity patient simulations may be effective in improving nursing students’ knowledge and performance [ 5 ], enhancing their self-confidence in performing nursing care, and reducing anxiety [ 6 ].…”
Section: Introductionmentioning
confidence: 99%